THE ROLE OF MARKETING REPRESENTATIVE AS TALKERS IN BUILDING WORD OF MOUTH AT BUNDA MULIA UNIVERSITY AS A SUPPORTING IN MARKETING COMMUNICATION ACTIVITIES - Indra Novianto Adibayu Pamungkas (SEMIOTIKA: Jurnal Komunikasi, 2014)
Word of Mouth Marketing became one of the most trusted elements compared to other types of advertising. This is due to the delivery of messages can be directly from the people who have credibility in delivering his message to another people. Talkers are those who send messages to others in volunteer manner. Universitas BundaMulia (UBM) is one of the leading universities in Indonesia and has marketing Communication programs are carried out. One of them using the service marketing representative. Through this study, the researchers wanted to know the role of marketing representative as talkers in the delivery of activities of word of mouth. In this research, the researcher uses the paradigm of post positivism and qualitative research method. Researchers use methods of in-depth interviews to Marketing Representative from among the students at UBM. The results of this research are basically marketing representative at UBM can be categorized as a happy customer and this became one of the conditions as good talkers. But the need for the development of the topic for the talkers to talk about UBM. Word of mouth happens online via social media but tacking part happens both offline and online. Talkers a little due to word of mouth tracking occurs by itself without any intention as marketing activities.Keywords: Word of Mouth, Word of Mouth Marketing, Marketing Communication, Talkers